MiR-134-3p targets HMOX1 to inhibit ferroptosis in granulosa cells of sheep follicles - Gulimire Abudureyimu; Yangsheng Wu; Ying Chen; Liqin Wang; Geng Hao; Jianguo Yu; Jianguo Wang; Jiapeng Lin; Juncheng Huang (BMC, 2024)
Abstract Background The intricate interplay of gene expression within ovarian granulosa cells (GCs) is not fully understood. This study aimed to investigate the miRNA regulatory mechanisms of ferroptosis during the process of follicle development in lamb GCs. Methods Employing transcriptome sequencing, we compared differentially expressed mRNAs (DE-mRNAs) and miRNAs (DE-miRNAs) in GCs from lambs treated with follicle-stimulating hormone (FL) to untreated controls (CL). We further screened differentially expressed ferroptosis-related genes and identified potential miRNA regulatory factors. The expression patterns of HMOX1 and miRNAs in GCs were validated using qRT‒PCR and Western blotting. Additionally, we investigated the regulatory effect of oar-miR-134-3p on HMOX1 and its function in ferroptosis through cell transfection and erastin treatment. Results We identified a total of 4,184 DE-mRNAs and 304 DE-miRNAs. The DE-mRNAs were mainly enriched in ferroptosis, insulin resistance, and the cell cycle. Specifically, we focused on the differential expression of ferroptosis-related genes. Notably, the ferroptosis-related genes HMOX1 and SLC3A2, modulated by DE-miRNAs, were markedly suppressed in FLs. Experimental validation revealed that HMOX1 was significantly downregulated in FL and large follicles, while oar-miR-134-3p was significantly upregulated compared to that in the CLs. HMOX1 expression was regulated by the targeting effect of oar-miR-134-3p. Functional assays further revealed that modulation of oar-miR-134-3p influenced HMOX1 expression and altered cellular responses to ferroptosis induction by erastin. Conclusion This study suggested that oar-miR-134-3p and HMOX1 may be one of the pathways regulating ferroptosis in GCs. This finding provides new clues to understanding the development and regulatory process of follicles.